The rules of magic - Hoffman, Alice 1952- (Simon & Schuster Paperbacks, 2017)
"The prequel to Alice Hoffman's PRACTICAL MAGIC, following the lives of Franny and Jet Owens (and their brother Vincent Owens) long before Sally and Gillian wound up on their doorstep"...
Keywords: Fantastic fiction / gsafd; Witches -- Fiction